PENERAPAN MODEL PROBLEM BASED LEARNING UNTUK MENINGKATKAN HASIL BELAJAR BAHASA INDONESIA SISWA KELAS V SDN 03 BENGKAYANG - Ayu; Kusnanto (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study aimed to improve the learning outcomes of fifth grade students in Indonesian language subjects through the application of the Problem Based Learning (PBL) model at SDN 03 Bengkayang. This research used Classroom Action Research (CAR) consisting of two cycles, where each cycle included planning, action, observation, and reflection stages. The subjects of this study were 34 fifth grade students consisting of 17 male students and 17 female students. Data collection techniques used in this study were observation, tests, and documentation. The results showed that the application of the Problem Based Learning model was able to improve students’ learning outcomes in Indonesian language learning. This improvement could be seen from the increase in the average score and classical learning completeness in each cycle. In the pre-cycle stage, the average student score was 51.5 with a learning completeness percentage of 26.47%. In Cycle I, the average score increased to 59.85 with a completeness percentage of 41.18%. Furthermore, in Cycle II, the average score increased to 75.14 with a completeness percentage of 82.35%. In addition, students’ learning activities also increased during the learning process. Therefore, the Problem Based Learning model can be used as an effective learning alternative to improve Indonesian language learning outcomes in elementary schools.